FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAAN PENYAKIT FILARIASIS PADA MASYARAKAT DI KECAMATAN BONANG KABUPATEN DEMAK - Febri Iswanto; Emmy Riyanti; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Masyarakat (Undip), 2017)
Filarial disease is a health problem in Bonang District Demak Regency with 10 clinical cases of filarial disease in 2015 and there is still possibility of transmission. Behavioral factor needs to be discovered as the basis to find out the preventive action. The purpose of this research was to analyze fators related with preventive behavior of filarial diseasein the community at Boonang District Demak Regency.This was a cross sectional design with accidental sampling technique to obtain research samples of 85 people in Bonang District Magolinduk Village and Wonosari Village. Data was collected using questionnaire interview. Data was analyzed using univariate and bivariate with chi-square test. The results showed that most of the respondents were 18-40 years old (70,6%) and majority of the respondents were not doing prevention of filarial disease (61,2%). Chi square test result showed that knowledge of preventive behavior of filarial disease (p=0,011), attitude about preventive behavior of filarial disease (p=0,000), exposure of information about preventive behavior of filarial disease (p=0,001), family support about preventive behavior of filarial disease (p=0,033) and health officer support about preventive behavior of filarial disease (p=0,001) were significantly correlated with preventive behavior of filarial disease. While age (p=0,070), sex (p=0,641), respondents education (p=0,089), job (p=0,529), and public figure (p=0,716) were not significantly correlated with preventive behavior of filarial disease in the community at Bonang District Demak Regency. Therefore prevention of filarial disease that could be implemented in Bonang District Demak Regency was giving counseling about preventive behavior of filarial disease particularly about using the mosquito net and hanging the clothes.